Postoperative outcome and quality of life after surgery for FAP-associated duodenal adenomatosis - Ganschow, Petra; Hackert, Thilo; Biegler, Marcel A.; Contin, Pietro; Hinz, Ulf; Büchler, Markus W.; Kadmon, Martina (Langenbeck's archives of surgery, 2018)
IntroductionProphylactic colon surgery has increased life expectancy of familial adenomatous polyposis patients. Extracolonic manifestations are life limiting, above all duodenal adenomas. Severe duodenal adenomatosis or cancer may necessitate pancreas-preserving total duodenectomy or partial pancreatico-duodenectomy, mostly after previous proctocolectomy and often after limited local resections of duodenal adenomas.Scarce information on long-term postoperative outcome and quality of life after surgery for duodenal adenomatosis is available. Aim of the present study was to analyze perioperative and long-term outcome after PD and PPTD for FAP-associated duodenal adenomatosis, including QoL and recurrence of adenomas in the neoduodenum after PPTD.Material, methods and patientsThirty-eight patients, 27 after pancreas-preserving duodenectomy and 11 after partial pancreaticoduodenectomy, were included.ResultsPancreas-preserving total duodenectomy was associated with shorter operation time and less blood loss than partial pancreatico-duodenectomy. Clinically relevant pancreatic fistula occurred in 31.5%. In-hospital mortality was 5.3%. Long-term follow-up revealed recurrent pancreatitis after pancreas-preserving total duodenectomy in 22% of patients, two (7.4%) required re-operation. Recurrent adenomatosis was detected in 26% of patients. Quality of life was comparable to the German normal population after both surgical procedures. Patients with postoperative complications showed worse results than those without complications. Disease-specific 10-year survival rate with respect to duodenal adenomatosis was 100%.ConclusionSurgery for FAP-associated duodenal adenomatosis and cancer can be carried out with reasonable morbidity rates despite previous proctocolectomy. Long-term outcome, quality of life, and survival rates are favorable.